Gene modification strategies using AO‐mediated exon skipping and CRISPR/Cas9 as potential therapies for Duchenne muscular dystrophy patients. Issue 3 (9th December 2020) - Solberg, Marthe Helene; Shariatzadeh, Maryam; Wilson, Samantha L
Abstract : Duchenne muscular dystrophy (DMD) is an X‐linked genetic disease affecting 1 in 5000 young males worldwide annually. Patients experience muscle weakness and loss of ambulation at an early age, with ∼75% reduced life expectancy. Recently developed genetic editing strategies aim to convert severe DMD phenotypes to a milder disease course. Among these, the antisense oligonucleotide (AO)‐mediated exon skipping and the adeno‐associated viral‐delivered clustered regularly interspaced short palindromic repeat (CRISPR) associated protein 9 (adeno‐associated viral (AAV)‐delivered CRISPR/Cas9) gene editing have shown promising results in restoring dystrophin protein expression and functionality in skeletal and heart muscle in both animals and human cells in vivo and in vitro. However, therapeutic benefits currently remain unclear. The aim of this review is to compare the potential therapeutic benefits, efficacy, safety, and clinical progress of AO‐mediated exon skipping and CRISPR/Cas9 gene‐editing strategies. Both techniques have demonstrated therapeutic benefit and long‐term efficacy in clinical trials. AAV‐delivery of CRISPR/Cas9 may potentially correct disease‐causing mutations following a single treatment compared to the required continuous AO/PMO‐delivery of exon skipping drugs. The latter has the potential to increase the dystrophin expression in skeletal/heart muscle with sustained effects. However, therapeutic challenges including the need for optimised delivery must be overcome in to advance current clinical data.